THE IDENTIFICATION OF LOGICAL THINKING ABILITY BASED ON GENDER IN PHYSICS TEACHERS PROSPECTIVE STUDENTS - Manurung, Sondang R; Panggabean, Deo Demonta (Journal of Community Research and Service, 2018)
AbstractThe purpose of this study is to examine the ability to think logically in physics teachers candidates based on gender. The study was carried out in Medan State University that is acknowledged as one of leading Teaching-based Institution (locally known as Lembaga Pendidikan Tenaga Kependidikan, henceforth abbreviated as LPTK) in Medan. This research used an instrument that further examining the Test of Logical Thinking (TOLT). The total research sample is 70 people, consisting of 27 male and 43 female students. The results showed that male students have a higher logical thinking ability than female students. The implication of the result is discussed.Keywords: Logical Thinking, Gender, Physics Teachers Prospective Student, Medan State University